The production of space and socio-environmental relations in the Middle Juruá: the construction of another governance (Research, Society and Development, 2022)
This article aimed to analyze the space production in the Middle Juruá territory from the governance of social organizations that work in the sociobiodiversity chains in the region. The episteme used in this study was the production of space. The study was carried out from a bibliographic survey on the region, documental and field research data collection with the main actors of the region. The Middle Juruá territory is marked by a history of workers oppression in the rubber economic cycles, but also by a process of struggles and social constructions that changed the form of social and environmental relations in the region. This process triggered the creation of two conservation units for sustainable use: RESEX of Middle Juruá and RDS Uacari. The socio-bio-diversity chains represent an important tool for the region sustainability, generating income and guaranteeing improvements to the quality of life. The empowerment process for the creation of social organizations was a precursor in the production of space in the Middle Juruá and in the sustainable use of the region's natural resources.